Determinants of Tax Compliance Among E-Commerce Entrepreneurs in Sidoarjo: Faktor-Faktor yang Mempengaruhi Kepatuhan Pajak di Kalangan Pengusaha E-Commerce di Sidoarjo - Jannah , Miftakhul; Biduri, Sarwendah (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: The rapid growth of e-commerce in Indonesia has created new challenges in tax compliance among online business actors. Specific Background: Despite increasing digital transactions, tax compliance among e-commerce entrepreneurs remains inconsistent. Knowledge Gap: Limited empirical evidence explains how regulatory understanding, tax rates, environment, and taxpayer awareness jointly shape tax compliance in local e-commerce sectors. Aims: This study aims to examine the relationship between tax regulation understanding, tax rates, environment, taxpayer awareness, and tax compliance among e-commerce entrepreneurs in Sidoarjo. Results: Using multiple linear regression on 40 respondents, all independent variables showed positive and significant relationships with tax compliance. Novelty: This study provides localized empirical evidence on behavioral tax compliance within micro-scale e-commerce enterprises. Implications: The findings offer strategic insights for policymakers in strengthening digital tax compliance through education and social support mechanisms. Highlights: Tax awareness strengthens compliance behavior Social environment shapes tax obedience Digital entrepreneurs require regulatory literacy Keywords: Tax Compliance, E-Commerce Taxation, Tax Awareness, Tax Regulations, Digital Entrepreneurs